2020
DOI: 10.1063/1.5142408
|View full text |Cite
|
Sign up to set email alerts
|

Effect of geometric parameters on synthetic jet: A review

Abstract: A synthetic jet actuator is a fluidic device that produces a jet flow by the periodic ingestion of fluid into and expulsion of fluid out of a cavity across an orifice. Since such a mechanism transfers linear momentum to the fluid without introducing a net mass into the system over an actuation cycle, the synthesised jet is also termed a zero-net-mass-flux jet. Over the last two decades, synthetic jets have been the subject of intense research. It has been shown that the geometric parameters of a synthetic jet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…SJAs can make large-scale alterations to the flow field relative to its characteristic length scale [13]. The layout of a SJA consists of an orifice with width d, a cavity, and an actuator to drive the fluid motion, which can be piezoelectric, electromagnetic, acoustic, or a mechanical device [14]. The layout of the SJA used in this current study is shown in Figure 1a for reference.…”
Section: Synthetic Jet Actuatorsmentioning
confidence: 99%
“…SJAs can make large-scale alterations to the flow field relative to its characteristic length scale [13]. The layout of a SJA consists of an orifice with width d, a cavity, and an actuator to drive the fluid motion, which can be piezoelectric, electromagnetic, acoustic, or a mechanical device [14]. The layout of the SJA used in this current study is shown in Figure 1a for reference.…”
Section: Synthetic Jet Actuatorsmentioning
confidence: 99%
“…Transcossi et al [41] presented a numeric as well as the theoretical concept of the Coanda effect that can be used for aeronautical naval propulsion and industrial applications. The impact of the geometric parameters like height, diameters of the cavity as well as the orifice, shape, and edge configuration of the orifice on the performance of the SJA is discussed in [42]. SJA-based numerical simulation is carried out to improve the aerodynamics efficiency of the flying wing aircraft [43].…”
Section: Introductionmentioning
confidence: 99%
“…The use of more than one movable or deformable element is also possible and beneficial [3,4], but this can cause a significant increase in the actuator size especially in the case of mechanics and acoustic actuators, and limit their applicability. The modification of SJA cavity dimensions [5] and shape [6] both have an impact on the produced SJ, but the modification of the orifice is much easier and more important in terms of SJA application and design than the other two possibilities. The modification and increasing of the SJA parameters are important, especially for their application.…”
Section: Introductionmentioning
confidence: 99%